Peran Bahasa (Indonesia) Dalam Menjaga Keberlanjutan Lingkungan Hidup - Abdul Hamid (Universitas Palangka Raya, 2023)
Sustainable development goals (SDGs) are not something new. SDGs has been going on for a very long time, both nationally and internationally. One of the goals of sustainable development is about the environment, about achieving sustainable management of natural resources and the environment as a support for all life. Various issues related to the environment are still ongoing. The waste problem is still being discussed, so in 2020 the government will issue regulations regarding waste management. In Indonesian, the jargon has long been known,